Prey availability and ambient temperature influence carrion persistence in the boreal forest. Issue 9 (19th July 2020) - Peers, Michael J. L.; Konkolics, Sean M.; Lamb, Clayton T.; Majchrzak, Yasmine N.; Menzies, Allyson K.; Studd, Emily K.; Boonstra, Rudy; Kenney, Alice J.; Krebs, Charles J.; Martinig, April Robin; McCulloch, Baily; Silva, Joseph; et al.
Abstract: Scavenging by vertebrates can have important impacts on food web stability and persistence, and can alter the distribution of nutrients throughout the landscape. However, scavenging communities have been understudied in most regions around the globe, and we lack understanding of the biotic drivers of vertebrate scavenging dynamics. In this paper, we examined how changes in prey density and carrion biomass caused by population cycles of a primary prey species, the snowshoe hare Lepus americanus, influence scavenging communities in the northern boreal forest. We further examined the impact of habitat and temperature on scavenging dynamics. We monitored the persistence time, time until first scavenger, and number of species scavenging experimentally‐placed hare carcasses over four consecutive years in the southwestern Yukon. We simultaneously monitored hare density and carrion biomass to examine their influence relative to temperature, habitat, and seasonal effects. For the primary scavengers, we developed species‐specific scavenging models to determine variation on the effects of these factors across species, and determine which species may be driving temporal patterns in the entire community. We found that the efficiency of the scavenging community was affected by hare density, with carcass persistence decreasing when snowshoe hare densities declined, mainly due to increased scavenging rates by Canada lynx Lynx canadensis . However, prey density did not influence the number of species scavenging a given carcass, suggesting prey abundance affects carrion recycling but not necessarily the number of connections in the food web. In addition, scavenging rates increased in warmer temperatures, and there were strong seasonal effects on the richness of the vertebrate scavenging community. Our results demonstrate that vertebrate scavenging communities are sensitive to changes in species' demography and environmental change, and that future assessments of food web dynamics should consider links established through scavenging. Abstract : This paper demonstrates that population cycles of snowshoe hares can influence the efficiency of carrion recycling by impacting vertebrate scavenging communities. Carrion persistence decreased when snowshoe hare densities declined, likely through increased scavenging by Canada lynx. Vertebrate scavenging rates in the boreal forest also increased in warmer temperatures.